Flavonoids: A Potential For Sustainable Agriculture - Biswas, Chandra; Bhattacharyya, Chinmoyee (The Flavonoids, 2024)
Flavonoids are a large group of polyhydroxy flavonoid derivatives synthesized widely in plants. Their health benefits have been documented for more than 150 years, with the first published article on the subject appearing in 1870. Throughout this time, there has been an ongoing debate on how they work biologically. There are over 4000 flavonoids discovered to date, with the vast majority of these being dietary products found in fruits, vegetables, and herbs. Only a small fraction of them has been shown to be pharmacologic. In plants, flavonoids are capable of preventing oxidative reactions in plant tissues and providing protection against UV radiation, drought, and salt stress. They also play a significant role in plant-microbe interactions, pollination, and in prevention of pests and other microorganisms. Majority of Indian population lives on agriculture as the country is blessed with fertile land and suitable climate for growing crops. Though this field gains a generous amount of income, but every year it faces a huge loss due to drought, attack of pests, weeds, and diseases, and to mitigate these, synthetic chemicals are used that can have adverse side effects in the long run. Finding a natural alternative strategy for preventing biotic and abiotic stresses in 296paddy fields is a demand of time. Flavonoids can be a very effective potential candidate for finding a natural way. Using this versatile low molecular weight chemical for environment-friendly and sustainable agriculture is of utmost concern as the synthetic chemical fertilizers/pesticides are not only expensive but also detrimental for the environment and human health. This chapter aims to discuss the role played by flavonoids in plants and its potential use in agriculture. This chapter discusses the biological roles of flavonoids in plants and their application to improve the agricultural sector using natural products while reducing the health hazards and environmental stresses due to the use of conventional synthetic chemicals. There are diverse groups of flavonoids based on where the aromatic ring is attached; among which flavonoids and flavones are most commonly found in plants, while distribution of others such as flavanols, flavanones, dihydrochalcones, and dihydroflavones is limited. Plant growth and development are aided by flavonoids in both direct and indirect ways. Plants are resistant to UV radiation because flavonoids (anthocyanin) filter UVB by absorbing it and detoxify the reactive oxygen species processed by photochemical reactions. Recently, a study showed that among the five phenolic compounds found in the extract of Tunisian plants, three were flavonoids which have showed significant herbicidal activity against Trifolium incarnatum by preventing seed germination and growth of the saplings.